Crystal structure of chlorido-(5-nitro-2-phenylpyridine-κ2N,C)-[(methylsulfinyl)methane-κ1S]platinum(II), C13H13ClN2O3PtS - Zou Hao; Tan Wei; Zhang Jian-Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C13H13ClN2O3PtS, monoclinic, C2/c (no. 15), a = 7.9405(8) Å, b = 18.0744(18) Å, c = 21.513(2) Å, β = 98.781(1)∘, Z = 8, V = 3051.3(5) Å3, Rgt(F) = 0.0535, wRref(F2) = 0.0233, T = 296 K.